Plague and long-term development: the lasting effects of the 1629-30 epidemic on the Italian cities - Guido Alfani; Marco Percoco (European Historical Economics Society (EHES), 2016)
The paper aims to analyze the effects of plague on the long-term development of Italian cities, with particular attention to the 1629-30 epidemic. By using a new dataset on plague mortality rates in 49 cities covering the period 1575-1700 ca., an economic geography model verifying the existence of multiple equilibria is estimated. It is found that cities severely affected by the 1629-30 plague were permanently displaced to a lower growth path. It is also found that plague caused a long-lasting damage to the size of Italian urban populations and to urbanization rates. These findings support the hypothesis that seventeenth-century plagues played a fundamental role in triggering the process of relative decline of the Italian economies.
Keywords: N30; N33; N93; D31; 330; Plague; Italian cities; Urban development; Urban demography; Multiple equilibria; Early modern period; Mortality crises; Urbanization; Italy